Penerapan Business Model Canvas dalam Mewujudkan Keberlanjutan Usaha Jual Beli Hasil Bumi - Siva Khoerunisa; Rohimat Nurhasan; Hilman Rismanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the application of business models using the nine elements of the Business Model Canvas (BMC) combined with SWOT analysis. This study uses a descriptive qualitative method conducted through interviews and observations of business owners. The results of the study show that the business has strengths in its strategic location, product quality, excellent service, customer trust, good relationships with suppliers and customers, and commitment to providing guarantees, but weaknesses in internal management that is not yet efficient and well structured. The analysis indicates a strong internal and external position, placing the business in an aggressive (SO) strategy that prioritizes the utilization of internal strengths to seize external opportunities. Strategic recommendations include improving service quality and strengthening relationships to expand the market, maximizing quality and providing warranties for damaged goods to open new partnerships, and maintaining relationships with suppliers to ensure a steady supply of goods. These findings confirm that Business Model Canvas (BMC) and SWOT analysis are effective in formulating strategies to support business sustainability.